Development of instruments to assess the achievement of national competencies at the end of primary education cycle - Nath, Samir Ranjan; Ghosh, Sanat Kumar; Akter, Shaheen (BRAC Research and Evaluation Division (RED), 2020)
This report presents a detailed description of development of assessment tools for the evaluation of students' learning achievement on the basis of 53 terminal competencies specified by the National Curriculum and Textbook Board (NCTB) of the Government of Bangladesh. This is the first attempt in the country to cover all the terminal competencies in assessment process. A team of school-teachers, teacher educators, curriculum experts, education psychologists, test development experts participated in the process. The competencies were divided into two broad categories viz., cognitive and non-cognitive. Two separate tools were developed for assessing the two types of competencies on the basis of pilot studies in both rural and urban areas. For the cognitive competencies a paper and pencil based test instrument containing 66 items was developed. For the assessment of non-cognitive competencies a tool was developed to have teachers' appraisal of students qualifications. It is expected that valid and reliable estimates of students' performance could be obtained through these tools.